Characterization and effect of metal ions on the formation of the Thermus thermophilus Sco mixed disulfide intermediate - Lopez, Liezelle C. (Protein Sci, 2018)
The Sco protein from Thermus thermophilus has previously been shown to perform a disulfide bond reduction in the Cu(A) protein from T. thermophilus, which is a soluble protein engineered from subunit II of cytochrome ba (3) oxidase that lacks the transmembrane helix. The native cysteines on TtSco and TtCu(A) were mutated to serine residues to probe the reactivities of the individual cysteines. Conjugation of TNB to the remaining cysteine in TtCu(A) and subsequent release upon incubation with the complementary TtSco protein demonstrated the formation of the mixed disulfide intermediate. The cysteine of TtSco that attacks the disulfide bond in the target TtCu(A) protein was determined to be TtSco Cysteine 49. This cysteine is likely more reactive than Cysteine 53 due to a higher degree of solvent exposure. Removal of the metal binding histidine, His 139, does not change MDI formation. However, altering the arginine adjacent to the reactive cysteine in Sco (Arginine 48) does alter the formation of the MDI. Binding of Cu(2+) or Cu(+) to TtSco prior to reaction with TtCu(A) was found to preclude formation of the mixed disulfide intermediate. These results shed light on a mechanism of disulfide bond reduction by the TtSco protein and may point to a possible role of metal binding in regulating the activity. IMPORTANCE: The function of Sco is at the center of many studies. The disulfide bond reduction in Cu(A) by Sco is investigated herein and the effect of metal ions on the ability to reduce and form a mixed disulfide intermediate are also probed.